Redefining Chinese talent management in a new context: a talent value theory perspective. (23rd December 2021) - Wang, Meng; Xu, Jiuping; Zhao, Shuming; Bian, Huimin
Abstract : The boundaries of talent management (TM) are shifting. However, there remains insufficient understanding of the impact of context and stakeholders within the conceptualisation of TM. Considerable confusion remains about how TM is conceived and defined in the Chinese context. Even less is known about how to reconceptualise Chinese TM in a changing new context. This review adopts a new theoretical lens of talent value to reconsider the current definitions of Chinese TM and presents a framework for re‐examining the relationships between the components of Chinese TM. Integrating the findings of the academic and practical literature, this article proposes a model to identify key contextual factors of the new context to observe and analyse the impacts of contextual changes on the concept of Chinese TM. By reviewing the English and Chinese literature on TM in the Chinese context, we bridge the knowledge gap and provide non‐Chinese readers with insights into the Chinese TM phenomenon and ways of conceptualisation that will be relevant to multinational firms operating in China and cross‐country comparative studies.